Design and experiment verification of a new heavy friction-stir-weld robot for large-scale complex surface structures. Issue 4 (15th June 2015) - Wu, Jiafeng; Zhang, Rui; Yang, Guangxin
Abstract : Purpose: – This paper aims to present a new friction-stir-weld robot for large-scale complex surface structures, which has high stiffness and good flexibility. Design/methodology/approach: – The robot system is designed according to manufacturability of large aluminum products in aeronautic and astronautic area. The kinematic model of the robot is established, and a welding trajectory planning method is also developed and verified by experiments. Findings: – Experimental results show that the robot system can meet the requirements of friction stir welding (FSW) for large-scale complex surface structures. Practical implications: – Compared with other heavy robotic arm and machine tool welding devices, this robot has better working quality and capability, which can greatly improve the manufacturability for large-scale complex surface structures. Originality/value: – The friction-stir-weld robot system is a novel solution for welding large-scale complex surface structures. Its major advantages are the high stiffness, good flexibility and high precision of the robot body, which can meet the requirements of FSW. Besides, a welding trajectory planning method based on iterative closest point (ICP) algorithm is used for welding trajectory.